Mathematical modeling of preparation of emulsions such as "oil / water" - Lugovska, Oksana; Sidor, Vasyl (My University, 2016)
Past studies on the effect of the number of emulsifiers in emulsion characteristics obtained showed that changing the fate of particle distribution depending on the particle size emulsion close to Gaussian distribution.Constructed one factor models the size distribution of particles of starch and gum arabic stabilizer in emulsions.
Keywords: кафедра експертизи харчових продуктів; emulsion; phase; starch; gum Arabic; mathematical modeling; математичне моделювання; етапи; крохмаль; емульсії; гуміарабік; математическое моделирование; эмульсии; этапы; крахмал; гуммиарабик